Reasoning about alternative forms is costly: The processing of null and overt pronouns in Italian using pupillary responses. Issue 2 (7th February 2020) - Vogelzang, Margreet; Foppolo, Francesca; Guasti, Maria Teresa; van Rijn, Hedderik; Hendriks, Petra
ABSTRACT: Different words generally have different meanings. However, some words seemingly share similar meanings. An example are null and overt pronouns in Italian, which both refer to an individual in the discourse. Is the interpretation and processing of a form affected by the existence of another form with a similar meaning? With a pupillary response study, we show that null and overt pronouns are processed differently. Specifically, null pronouns are found to be less costly to process than overt pronouns. We argue that this difference is caused by an additional reasoning step that is needed to process marked overt pronouns but not unmarked null pronouns. A comparison with data from Dutch, a language with overt but no null pronouns, demonstrates that Italian pronouns are processed differently from Dutch pronouns. These findings suggest that the processing of a marked form is influenced by alternative forms within the same language, making its processing costly.